INTERAKSI VERBAL PADA KOMUNIKASI AKADEMIK DOSEN PEMBIMBING AKADEMIK: STUDI KASUS MAHASISWA PBI FKIP UNIVERSITAS MUHAMMADIYAH SURAKARTA - Dini Restiyanti Pratiwi (BAHASTRA, 2017)
The study aims to describe 1) the academic interaction and 2) communication form between the students and their academic lecturers of the Study Program of Indonesian Language Education, Faculty of Trainer and Training Education, Universitas Muhammadiyah Surakarta. It employed a descriptive-qualitative approach. The data collection used the techniques of in-depth interview, observation, and documentation. The data sources were obtained from the the students and their lecturers. The data were the academic interaction and communication forms. The data validity applied a data or source triangulation. The data analysis employed an interactive model: data reduction, data display, and conclusion. The results of the study show that the academic interaction and communication form consist of informative, persuasive, and argumentative verbal. Furthermore, the forms are in a one-way, two-way, and multiple-way communications.